Factors affecting mammal utilisation of non-wildlife railway underpasses within the Greater Kruger, South Africa - de Villiers, Hannah (University of the Witwatersrand, Johannesburg, 2023)
Railways are an integral component of sustainable transport systems, but cause significant impacts to biodiversity, primarily through wildlife-train collisions and the habitat fragmentation created in the landscape. Crossing structures (CSs) for wildlife are the key mitigation measure for these adverse impacts, which will be critical throughout Africa, where 55,000 km of new railway lines are predicted to cut through hundreds of protected areas. For the first time in southern Africa, mammal usage of railway underpasses that were not designed to facilitate wildlife movement was studied using camera traps in the Greater Kruger National Park, South Africa. This study demonstrates that 70% of the terrestrial medium and large mammals species present in the area used at least one non-wildlife CS during the study period, with a total of 1,823 usage events by 33 species. Twelve medium to large African mammal species used underpasses regularly, improving the permeability of the railway line for these species. A viaduct design was characterised by almost four times the usage rate of a typical box culvert and was used by twice as many species, including megaherbivores and mesoherbivores, whereas box culverts supported a smaller number of species, of which the majority were predators. Species most affected by rail collisions in the study area were mostly herbivorous and seldom used non-wildlife underpasses. These results indicate that a railway line with only drainage culverts and the occasional viaduct is not effective in providing adequate safe crossing structures for megaherbivores and ungulate mesoherbivores. Contrary to expectations, vegetation and environmental factors influenced mammal usage of box culverts more than structural dimensions. Ensuring that there is high visibility through the structure, with less herbaceous cover and more woody cover outside of entrances, is likely to enhance culvert usage by most trophic groups. In a savanna context where faunal diversity is high and no single species is a target for mitigation, a range of underpass designs including larger viaducts, located in different types of vegetation cover, thereby combining the range of requirements of different guilds, is recommended.
Research report submitted in partial fulfilment of the requirements for the degree, Master of Science (Resource Conservation Biology), to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Railways; Rail; Underpass; Culvert; Mitigation; Linear infrastructure; Transport; Crossing structure; Mammals; UCTD; SDG-13: Climate action